Regional Innovation Index of China: 2017 How Frontier Regions Innovate - Liu, Xielin (Springer Singapore, 2018)
The book aims to explore the regional innovation capability of China, especially how the frontier regions of China (Guangdong, Jiangsu, Beijing, Shanghai, Zhejiang and Tianjin) transform themselves from an investment-driven economy into an innovation-driven one. With detailed case, data and policy, we analyse the modes of each province and municipality from different perspectives such as comparative advantage in innovation, existing industrial base and culture, the government's innovation strategy, and industrial upgrading pattern.